Comparative assessment of different categories of absorption heat transformers in water desalination process - Parham, Kiyan; Khamooshi, Mehrdad; Daneshvar, Sahand; Assadi, Mohsen; Yari, Mortaza (Elsevier, 2016)
During the last decade, there has been a significant amount of research conducted on absorption heat pumps (AHPs). Second type AHPs, namely absorption heat transformers (AHTs) are useful devices, capable of raising the temperature of waste heat to more useful temperature levels. The excluded heat from AHTs can provide the required energy for desalination. In the present work, performances of three main categories of AHT systems comprising single, double and triple absorption heat transformers (SAHT, DAHT, and TAHT) while they are coupled to water purification system are investigated and compared. A simulation model has been developed in EES (Engineering Equation Solver) to evaluate the effects of several key thermodynamic parameters on the performance of the cycle and amount of desalinated water. The results show that the highest gross temperature lift can be achieved with TAHT while it has the lowest COP among the other types of AHTs. Additionally, a performance optimization performed by using EES shows that SAHT, DAHT, and TAHT can provide fresh water for 853, 796 and 697 residential units respectively if they operate nonstop. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Absorption heat pump; Absorption heat transformer; Desalination; Additional stages; Energy efficiency